Acute Lymphoblastic Leukemia Presenting With Skin Rash And Forehead Swelling In A 31-Year-Old Male - Ali, Mohammad Moshfeq; Datta, Ponkaj; Rahman, Md Motlabur; Mitra, Anik; Khan, Md Abu Daud; Juhee, Fahmida An Nur; Habiba, Umme; Hossain, Md Ali (Journal of Dhaka Medical College, 2024)
Leukemia cutis is the infiltration of neoplastic leukocytes or their precursors into the epidermis, the dermis, or the subcutis of patients with leukemia, resulting in clinically identifiable cutaneous lesions. It is especially rare as the presenting symptom of leukemia and is associated with a poor prognosis. We present a case of acute lymphoblastic leukemia, whose initial complaints were skin lesions and forehead swelling, which we believe to be features of leukemia cutis. J Dhaka Med Coll. 2023; 32(1) : 96-98